Estimation of the heritability of medicinal compound contents in Glycyrrhiza uralensis - Takahiro Tsusaka; Miki Sakurai (PLoS ONE, 2025)
Glycyrrhiza uralensis Fischer (Fabaceae), an important medicinal plant widely used in traditional Japanese and Chinese medicine, contains bioactive compounds, such as glycyrrhizin and flavonoids, which exhibit pharmacological activities, including antispasmodic and antitussive effects. Overharvesting has depleted wild populations, making the cultivation of G. uralensis necessary to stabilize its supply; however, the content of bioactive compounds tends to decrease in cultivated plants. In this study, we investigated the genetic inheritance (heritability) of medicinal compound contents in G. uralensis by analyzing clonal lines propagated from stolons. Broad-sense heritability was estimated for seven medicinal compounds using 26 clonal lines, revealing high heritability for glycyrrhizin and several flavonoids. In addition, correlation analyses between seed-derived and stolon-derived roots demonstrated strong genetic inheritance of these compounds. Furthermore, the effects of plant age and cultivation year on compound content were examined. Our results show high correlations between compound content and genotype across plant age (one- and two-year-old plants), suggesting the feasibility of early selection in breeding programs. While environmental variations influenced absolute compound levels, the relative rankings among genotypes remained stable. These results indicate the high heritability of compound contents and the strong effectiveness of selective breeding. We conclude that there is strong potential for selective breeding to enhance the medicinal quality of G. uralensis by targeting high-yielding genotypes with superior compound profiles and that this potential may also apply to the sustainable cultivation of other high-quality medicinal plant resources.